Between persecution and participation : biography of a bookkeeper at J.A. Topf & Söhne - Schüle, Annegret, 1959-; Sowade, Tobias, 1988-; Milbouer, Penny (Syracuse, New York : Syracuse University Press, 2018)
This is the story of a crushingly ordinary man who had the misfortune to live in the first two-thirds of the twentieth century. The son of a baptized Jewish father and a Protestant mother, Willy Wiemokli (1908-1983) was declared a half-Jew by the laws of the Third Reich, and because of this, he and his father were briefly interned in Buchenwald. Although his father was eventually executed in Auschwitz in 1943, Willy went on to become an accountant for J. A. Topf & Söhne, the manufacturer of the ovens used in the death of his father as well as thousands of others in concentration camps. Persecuted by the Nazis, he also participated, minimally, in the Nazi-led genocide. This paradox and Willy's liminal status gives his fascinating biography historical significance, adding a new dimension to our understanding of what the Nazi race policies meant to ordinary Germans. In this brief telling of an otherwise average man's life, Schüle and Sowade reveal the pervasive and long-term effect of the race laws. Based solely on archival records, Willy's story gives insight into the muddled and impossible choices of vulnerable individuals living under the Third Reich and the blurred boundaries between victim, bystander, and accomplice.
C; Milbouer Final; bc.
Includes bibliographical references.
Online resource; title from digital title page (viewed on October 24, 2018).
JSTOR
Keywords: Wiemokli, Willy, -- 1908-1983.; Firma J.A. Topf & Söhne -- Employees; Firma J.A. Topf & Söhne; Accountants -- Germany -- Biography; Mischlinge (Nuremberg Laws of 1935) -- Germany -- Biography; Holocaust, Jewish (1939-1945); Comptables -- Allemagne -- Biographies; Mischlinge (Lois de Nuremberg, 1935) -- Allemagne -- Biographies; Holocauste, 1939-1945.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Europe -- Western; BIOGRAPHY & AUTOBIOGRAPHY -- General; Accountants; Employees; Mischlinge (Nuremberg Laws of 1935); Germany; 1939-1945; Biographies; Biographies; Biographies